Heraclitus, Plato, and the philosophic dogs (A note on Republic II, 375e-376c) (Revista Archai, 2015)
The paper focuses on a neglected instance of the Platonic reception of Heraclitus in the Republic (II, 375e-376c), trying to show that it’s likely that Plato’s passage makes an allusion to Heraclitus’ B97 (“Dogs bark at whom they don’t know”) and B85 (“It’s difficult to fight Î¸Ï…Î¼ÏŒÏ‚, for what it longs for it pays with ÏˆÏ…Ï‡Î®). The main claim is that Plato’s use of the image of dogs looks back to Heraclitus, which invites an exploration of the possibility that at least some elements of Plato’s kallipolis might derive from Heraclitus ”“ particularly from some ethical and political fragments. A brief survey of these suggests a deep philosophical affinity among the two authors in several important areas (as the so-called ‘moral psychology and ‘ethical intellectualism’), and questions the commonplace traditional interpretation of Heraclitus as a defender of aristocratic morality.